2020
DOI: 10.3748/wjg.v26.i28.4108
|View full text |Cite
|
Sign up to set email alerts
|

Food groups, diet quality and colorectal cancer risk in the Basque Country

Abstract: BACKGROUND The results obtained to date concerning food groups, diet quality and colorectal cancer (CRC) risk vary according to criteria used and the study populations. AIM To study the relationships between food groups, diet quality and CRC risk, in an adult population of the Basque Country (North of Spain). METHODS This observational study included 308 patients diagnosed with CRC and 308 age- and sex-matched subjects as controls. During rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The theoretical range of the HEISD is 0-100 and of the MDS 0-55; higher values of these scores indicate greater adherence to the dietary recommendations for the Spanish population and the Mediterranean diet pattern, respectively. These results were previously described [28].…”
Section: Dietary Habits Questionnairesupporting
confidence: 82%
See 1 more Smart Citation
“…The theoretical range of the HEISD is 0-100 and of the MDS 0-55; higher values of these scores indicate greater adherence to the dietary recommendations for the Spanish population and the Mediterranean diet pattern, respectively. These results were previously described [28].…”
Section: Dietary Habits Questionnairesupporting
confidence: 82%
“…The characteristics of the cases (pathological staging, location of the cancer, tumor grade and treatments) have been also described before [28]. Briefly, 72% were diagnosed with early-stage (I/II) CRC, 76% had distal location of the cancer, 80.5% of tumors were well-/moderately differentiated and 73.7% had undergone surgical resection.…”
Section: Sampling and Study Subjectsmentioning
confidence: 99%
“…However, the consumption level could be classified to a low intake according to the GBD study. A case–control study from the Basque Country indicated that a higher consumption of milk or dairy products was associated with an increased CRC risk, probably as a result of a small sample size ( n = 616) ( 16 ) . Meanwhile, the potential reasons for this were that cut‐offs for the highest milk or dairy product intake categories in different studies varied by geographical region, and also different studies had adjusted for different confounding factors, which biased the results and led to different estimates ( 50 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Most systematic reviews and meta‐analysis of prospective studies consistently showed a decreased risk of CRC associated with a higher consumption of milk or total dairy products ( 9,12–14 ) . However, some studies showed contradictory results ( 15,16 ) . In view of this, the Global Burden of Disease (GBD) study 2017 established the convincing causality for a diet low in milk–CRC pairing by systematically evaluating all existing epidemiological evidence and summarising the important characteristics of the relationship ( 17 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such association was observed in men, but not in women; this sex-disparity might depend on lower fiber intake registered for women (mean fiber intake of 14 g/day for women and 20.0 g/day for men) [ 118 ]. Alegria-Lertxundi and co-workers [ 115 ] investigated the relationships between food groups, diet quality and colorectal cancer risk and reported no significant differences of intake between control and patient groups for the majority of food classes, except for lower WG intake (and higher egg consumption) in tumor cases; coherently, the observed protective effects of fiber-containing foods appeared to be mainly ascribed to WGs. A recent, large US cohort analysis (with more than 10,000 incident colorectal cases and more than 15 years of follow-up) further confirmed that fiber from grains, but not from other sources, was associated with lower incidence, especially for distal colon and rectal cancers [ 116 ].…”
Section: Whole Grains and Colorectal Cancermentioning
confidence: 99%